2020
DOI: 10.3390/jcm9072123
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Surgery Elicits a Systemic Anti-Inflammatory Signature

Abstract: Little information is available on the functional activity of leukocytes after arthroplasty or the expansion of populations with immune suppressive properties during the acute post-operative period. Synovial fluid and matched pre- and post-surgical blood samples were collected from total hip and knee arthroplasty patients (THA and TKA, respectively) to examine the impact of surgery on peripheral blood leukocyte frequency, bactericidal activity, and inflammatory mediator expression. For spinal surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
2
13
1
Order By: Relevance
“…First, RA-TKA significantly shortened the time required for bone cutting and gap balancing: these durations were 5.3 min ( p = 0.010) and 2.2 min ( p = 0.021) shorter, respectively, with RA-TKA than with CM-TKA. The significance of this finding is that previous studies have shown that osteotomy error and repeated osteotomy during TKA can lead to excessive opening of the metaphyseal sinus, exhaustion of coagulation factors and progressive inflammatory cascade [ 21 , 22 ]. Second, although RA-TKA had a significantly longer total surgical time and operative time compared with CM-TKA, careful observation showed that the time increase was mainly concentrated in the preoperative planning and intraoperative registration stages.…”
Section: Discussionmentioning
confidence: 99%
“…First, RA-TKA significantly shortened the time required for bone cutting and gap balancing: these durations were 5.3 min ( p = 0.010) and 2.2 min ( p = 0.021) shorter, respectively, with RA-TKA than with CM-TKA. The significance of this finding is that previous studies have shown that osteotomy error and repeated osteotomy during TKA can lead to excessive opening of the metaphyseal sinus, exhaustion of coagulation factors and progressive inflammatory cascade [ 21 , 22 ]. Second, although RA-TKA had a significantly longer total surgical time and operative time compared with CM-TKA, careful observation showed that the time increase was mainly concentrated in the preoperative planning and intraoperative registration stages.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent years, CXCL1 was shown to be a product of the growth-regulated gene ( Gro ) [ 7 , 8 ]. Since then, CXCL1 has functioned under two names: MGSA and growth-regulated (or -related) oncogene (GRO) [ 8 , 9 , 10 ]. In the early 1990s, two more chemokines were identified that were very similar to GRO [ 11 ].…”
Section: The Name ‘ Cxcl1 ’mentioning
confidence: 99%
“…IL-10 is induced by lactate released from S. aureus biofilm, which inhibits HDAC11 to induce epigenetic changes at the Il-10 promoter as well as other genes ( 41 ). G-MDSCs are also enriched in humans during PJI, and are expanded in the blood following orthopedic infection ( 151 , 152 ). This suggests that they may play an important role in dictating infection persistence and/or susceptibility, respectively.…”
Section: Microglia and Myeloid Cells Associated With S Aurmentioning
confidence: 99%